The role of didactics in the post-digital age - Angelo Figliola (Agathón)
The birth of the first robotic manufacturing laboratory in 2005 at the Federal Polytechnic School of Zurich, ETH, under the direction of F. Gramazio and M. Kolher marked a new course for digital architecture manufacturing. The potentialities of this design methodology are investigated with respect to different lines of research that have in common the development of processes related to the definition of informed architectures. One of the crucial aspects is related to teaching, which is fundamental for developing and structuring the necessary skills that future operators should possess to allow the dissemination of the theme in architectural and executive practice.